Negotiating legitimacy and normalization of queer desires in Sello Duiker's The Quiet Violence of Dreams. Issue 1 (2nd January 2016) - Dlamini, Nonhlanhla
ABSTRACT: This paper argues that Sello Duiker's The Quiet Violence of Dreams (2001) unsettles the standard binarist discourses and tropes around creative and scholarly treatments of hetero/homosexualities. The novel does this by offering different ways of thinking about masculinities, the relationships they have with each other, and the social status they enjoy. Duiker's literary representation of homosexual masculinities problematizes Morrell and Connell's theorizations of masculinity. Instead of thinking about black homosexuality as a masculine and gendered identity which stands in opposition to heterosexuality as Morrell does (1998), the novel blurs the heterosexual/homosexual and man/woman gender and sex dichotomies. It depicts that the above identities are as neither distinct nor oppositional, rather their relationships are marked by grey areas: they intersect, overlap, and are relational to each other. This paper examines how The Quiet Violence of Dreams represents itself as a text that speaks back to the acclaimed absence of black homosexuality depicted in earlier South African literary texts published during apartheid era. It further examines the manner in which the novel uses literary devices and modes of narration such as mythopoeia, madness, and African spirituality to reimagine homosexuality in the contemporary South African social sphere. Some of the interesting questions that this work probes are as follows: what is the importance of the linkages and discontinuities between the past and the present, and the "sacred" and the "profane, " in the negotiation of a space of "legitimacy" for the homosexual in the contemporary era? What strategies does Duiker employ to question and destabilize gender and sexual identity paradigms into which subjects are hailed into?